Gambaran Kondisi Gangguan Stress Pasca Trauma Pada Perempuan Korban Kekerasan Dalam Hubungan Romantik - Anak Agung Ketut Sri Wiraswati; I Putu Galang Dharma Putra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Women have a deeper attachment when in a romantic relationship because they have an orientation towards having a mutually supportive relationship with their partner and gaining love and intimacy (Wiraswati, 2014). Violence against women is prone to causing post-traumatic stress disorder or PTSD. PTSD includes the emergence of unwanted intrusive thoughts, avoiding activities related to the traumatic experience, and exhibiting excessive emotional and physiological reactivity. In this study, interviews were conducted based on the PSSI-5 and mapping of the severity of PTSD symptoms using the Davidson Trauma Scale on three respondents. The research results showed that two respondents showed sub-clinical PTSD symptoms, while one other person showed high PTSD symptoms that interfered with daily activities. All respondents showed the emergence of PTSD symptoms including the emergence of repetitive intrusive thoughts without intention, avoiding stimuli that resemble traumatic events, feeling emotional dullness, and showing increased reactivity.